Analisis Produktvitas Dana Zakat Melalui Program Bedah Rumah di BAZNAS Kab. Pinrang - Nurul Ismayanti; Desy Arum Sunarta; Andi Bisyriani (STAI DDI Pinrang, 2025)
Zakat has an important role in economic and social aspects. On the one hand, zakat helps reduce poverty and fosters social awareness for the rich. On the other hand, zakat prevents the accumulation of wealth in a handful of people. Therefore, the role of the Zakat Agency is very much needed so that its distribution is right on target. This study aims to analyze the productivity of zakat funds through the house renovation program by BAZNAS Pinrang Regency. This type of research is descriptive qualitative with observation, interview, and documentation techniques for beneficiaries. The results of the study show that zakat funds are distributed through field parties who work together with BAZNAS, then organize the implementation of house renovation. Supporting factors of the program include a) Availability of definite funds, b) Transparency in reporting, and c) Good coordination between parties. While the inhibiting factors encountered are time issues, such as delays in the process of building houses for aid recipients.